1990
DOI: 10.1007/bf00199578
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß zentralnervöser koordination im Sinne v. HOLSTs auf die Steuerung von Atem- und Extremitätenmotorik des Menschen

Abstract: We found modulations in the time-course of breathing during rhythmic abduction-adduction movements in shoulder and hip joints which can be interpreted as phenomena of central coordination in the sense of v. Holst. They occurred in more than 75% of the recorded breaths. The strength of this coordination depends on number and kind of limbs moving rhythmically and on the use of an acoustic trigger signal ("Zeitgeber") for the limb rhythm as well. Our findings indicate that reactions of the respiratory apparatus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…Only a few of our subjects exhibited stable entrainment. This result was in agreement with other observations in this field (Hill et al 1988;Rassler et al 1990;van Alphen and Duffin 1994;Ebert et al 2000;Rassler and Kohl 2000). Total frequency of co-ordination (%C tot ) of 20% on average was slightly below the frequencies reported in the study of Ebert et al (2000) who investigated visually guided forearm tracking movements.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Only a few of our subjects exhibited stable entrainment. This result was in agreement with other observations in this field (Hill et al 1988;Rassler et al 1990;van Alphen and Duffin 1994;Ebert et al 2000;Rassler and Kohl 2000). Total frequency of co-ordination (%C tot ) of 20% on average was slightly below the frequencies reported in the study of Ebert et al (2000) who investigated visually guided forearm tracking movements.…”
Section: Discussionsupporting
confidence: 94%
“…In conditions ACT-O and PASS-O, they had to keep their eyes straight ahead. See Table 2 In earlier studies, we additionally observed numerous sequences of weak co-ordination reflecting the transition between independent and coordinated activity (Rassler et al 1990;Ebert et al 2000;Rassler and Kohl 2000). To disclose a wide range of coordination degrees we applied a modification of a criterion previously described by Ebert et al (2000).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…the amygdala complex [21,22,23]. Certain links between cardiovascular and respiratory rhythms have been shown [9,10,12,15,16,23,28,29,31,36,37,43,44]. Appearance and disappearance of such rhythms as well as the change in phase relations of 'relative coordination' are expression of continuously altering coordination of subsystems of the organism.…”
Section: Introductionmentioning
confidence: 99%